Hemifacial Spasm due to Compression of the Posterior Inferior Cerebellar Artery Aneurysm Treated with Botulinum Toxin Type-A: A Case Report - Azize Esra Gürsoy; Gülsen Babacan Yildiz; Adam Mehmet Gülhan; Mehmet Kolukisa (Case Reports in Neurological Medicine)
A 79-year-old female presented with five months history of progressive involuntary twitching movement on left face. Brain MR imaging revealed a heterogeneous T2 hyperintense lesion at left cerebellopontine angle. CT angiography showed a partially thrombosed saccular aneurysm of left PICA (posterior inferior cerebellar artery). The patient was treated with Botulinum toxin type A and almost total relief of symptoms was noticed during one month followup. Botulinium toxin injection is an effective symptomatic treatment option in nonsurgical secondary hemifacial spasm (HFS) cases.